Pengaruh Kinerja Portofolio Saham pada Indeks Sektoral Menggunakan Single Indeks Model - Restu Sugesti; Fitriasuri, Fitriasuri (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2024)
This article tries to collect and create an optimal portfolio empirically using the single index model. Next, to evaluate portfolio and market returns using the Sharpe, Jensen, and Treynor ratios. This research is based on secondary data that has been collected from www.yahoofinance.com, www.investing.com and www.Idx.com. Taking the Composite Stock Price Index (JCI), namely as the Market Performance Index (market) and using the Sectoral Index stock group in the 2022-2024 period as the population and sample. By taking the top 5 sectors (INFRA, ENERGY, BASIC, FINANCE, and HEALTH) and considering the monthly closing prices of the top 5 stocks in their sectors between June 1, 2022 to June 1, 2024, the cut-off point (C*) has been calculated and the selected securities to build an optimal portfolio with excess returns for ERBi greater than C*(ERBi>C*). This study shows that the optimal portfolio composition is to include CUAN 55.23%, BMRI 12.83%, BBCA 9.07%, SILO 8.25%, BREN 7.33%, JSMR 7.17%, MBMA 7.03%, ISAT 3.48%, KLBF 2.99%, TPIA 2.73%, BRPT 2.43%, and SIDO 0.28% of the amount invested by each sector has its own securities in the optimal portfolio. Portfolio valuation and market returns using the Sharpe, Jensen, and Treynor ratios show lower market returns than stocks. And Sharpe's measurement has a positive portfolio return and has the highest value of 1.00929 compared to Jensen's ratio of 0.172443 and Treynor which gives the lowest return of 0.024321.